Growing Plums in Florida - Mercy Olmstead; E. P. Miller; Peter C. Andersen; Jeffrey G. Williamson (EDIS, 2016)
Plums could be a potential crop for growers and homeowners in Florida and other mild winter areas throughout the Gulf coast, but many plum varieties will not grow well enough in Florida to produce fruit. In response to this need, the University of Florida has developed cultivars that improve the potential for growing plums in Florida. This revised 13-page fact sheet provides information for growing plums in Florida including information about chilling hours, pollination and fruit set, fruit harvesting, and yields, as well as information about the plum cultivars adapted to grow in Florida. Written by M. Olmstead, E.P. Miller, P.C. Andersen, and J.G. Williamson, and published by the Horticultural Sciences Department, January 2016.